Bootstrap and Jackknife Resampling Methods in Survival Analysis of Patients with Thalassemia Major - R Ali Akbari Khoei; E Bakhshi; A Azarkeivan; A Biglarian (مجله اپیدمیولوژی ایران, 2016)
Background and Objectives: A small sample size can influence the results of statistical analysis. A reduction in the sample size may happen due to different reasons, such as loss of information, i.e. existing missing value in some variables. This study aimed to apply bootstrap and jackknife resampling methods in survival analysis of thalassemia major patients.